2015
DOI: 10.1136/jmedgenet-2015-103399
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a pathogenicFTOmutation by next-generation sequencing in a newborn with growth retardation and developmental delay

Abstract: Our findings are consistent with previous reports that homozygous mutations in FTO can lead to rare growth retardation and developmental delay syndrome, and further support the proposal that FTO plays an important role in early development of human central nervous and cardiovascular systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 29 publications
2
42
0
Order By: Relevance
“…Nevertheless, these mice also display a considerable reduction in lean mass. Moreover, late-onset systemic deletion of Fto in the adult mouse also resulted in increased total fat mass and decreased lean mass (45), and individuals lacking FTO display growth retardation (30,31). In our study, congenital systemic Ftonull mice displayed reduced lean mass and elevated adiposity by 20 weeks of age (data not shown).…”
Section: Lepr-bmentioning
confidence: 75%
See 1 more Smart Citation
“…Nevertheless, these mice also display a considerable reduction in lean mass. Moreover, late-onset systemic deletion of Fto in the adult mouse also resulted in increased total fat mass and decreased lean mass (45), and individuals lacking FTO display growth retardation (30,31). In our study, congenital systemic Ftonull mice displayed reduced lean mass and elevated adiposity by 20 weeks of age (data not shown).…”
Section: Lepr-bmentioning
confidence: 75%
“…The reduction of hypothalamic FTO in fasted mice (18,19), and the in vivo findings presented above indicating that P200 overproduction decreased hypothalamic Fto expression and was associated with decreased energy expenditure and increased food intake, prompted us to test the hypothesis that Fto hypomorphism per se increases adiposity. We measured the body composition of mice systemically deleted for exon 3 of one Fto wild-type allele (Fto +/-) (29), as loss of both Fto copies results in severe loss of lean mass in mice and humans (29)(30)(31). Fto +/-male mice fed standard chow until the age of 14 weeks were approximately 16% heavier than control (+/+) mice ( Figure 3A; P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…To illustrate the application of the relationship described in Equation (13) to experimental data, we used GWAS data around the well-established obesity locus, FTO , generated by a recent large study of extreme BMI (Berndt et al, 2013). The FTO gene encodes for an alpha-ketoglutarate-dependent dioxygenase (Gerken et al, 2007), playing a role in growth and development (Boissel et al, 2009; Daoud et al, 2016), and has been reliably associated with the related conditions of type 2 diabetes, BMI, adiposity and other obesity-related traits (Scott et al, 2007; Zeggini et al, 2007; Lindgren et al, 2009; Thorleifsson et al, 2009; Fox et al, 2012; DIAGRAM Consortium et al, 2014; Wood et al, 2016). Within the FTO gene region, the study found that rs11075990 exhibited the strongest association with extreme BMI with a reported p -value of 9.3E-33.…”
Section: Resultsmentioning
confidence: 99%
“…To illustrate the application of the relationship described in Equation (13) to experimental data, we used GWAS data around the wellestablished obesity locus, FTO, generated by a recent large study of extreme BMI (Berndt et al, 2013). The FTO gene encodes for an alpha-ketoglutarate-dependent dioxygenase (Gerken et al, 2007), playing a role in growth and development (Boissel et al, 2009;Daoud et al, 2016), and has been reliably associated with the related conditions of type 2 diabetes, BMI, adiposity and other obesity-related traits (Scott et al, 2007;Zeggini et al, 2007;Lindgren et al, 2009;Thorleifsson et al, 2009;DIAGRAM Consortium et al, 2014;Wood et al, 2016). Within the FTO gene region, the study found that rs11075990 exhibited the strongest association with extreme BMI with a reported p-value of 9.3E-33.…”
Section: Application To Experimental Datamentioning
confidence: 99%